Analisis Pengendalian Kualitas Produk Karung di PT XYZ Menggunakan Metode Seven Tools - Supmana, Serly; Rian Prasetyo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
XYZ is a manufacturing company that produces Polypropylene Woven Bags (plastic sacks). This company uses a make to order production system. The aim of this research is to analyze the consequences of damaged products for plain white sacks and printed sacks in the cutting sawing division. The method used in this research is the seven tools method. From the seven tools analysis, namely the plain white BS sack type at 52% and the printed BS sack type at 48% and the most dominant was the plain white BS sack type with a number of defects of 2,333 pcs or 256.63 kg of sacks for 27 days in the cutting division. sawing. And from the results of the fishbone diagram, there are 5 main factors, namely: humans, machines, materials, methods and environment. The most dominant cause is the human factor. Operators who are less thorough and dexterous, operators who are less competent result in sacks being made that are not perfect, therefore quality control must be carried out on the product.